2012
DOI: 10.1100/2012/528593
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Peel Essential Oil Composition of Four Tunisian Citrus during Fruit Maturation

Abstract: The present work investigates the effect of ripening stage on the chemical composition of essential oil extracted from peel of four citrus: bitter orange (Citrus aurantium), lemon (Citrus limon), orange maltaise (Citrus sinensis), and mandarin (Citrus reticulate) and on their antibacterial activity. Essential oils yields varied during ripening from 0.46 to 2.70%, where mandarin was found to be the richest. Forty volatile compounds were identified. Limonene (67.90–90.95%) and 1,8-cineole (tr-14.72%) were the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
104
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(144 citation statements)
references
References 44 publications
20
104
4
1
Order By: Relevance
“…Comparison of limonene content of the peels essential oils (Table 1) indicates that the amount of limonene was increased during the fruit maturation, which is in agreement with the results of Bourgou et al (2012) in Tunisia. The variation in limonene content, from 59.88% to 91.76%, is possibly because of the decomposition of linalool and its acetate (13).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Comparison of limonene content of the peels essential oils (Table 1) indicates that the amount of limonene was increased during the fruit maturation, which is in agreement with the results of Bourgou et al (2012) in Tunisia. The variation in limonene content, from 59.88% to 91.76%, is possibly because of the decomposition of linalool and its acetate (13).…”
Section: Discussionsupporting
confidence: 79%
“…Several studies on the chemical composition of C. aurantium essential oils seem to be matched with our observation (16,17). GC-MS analysis of bitter orange leaf oil of north of Iran showed that linalool, linalyl acetate and alpha terpineol were the main components of the oil (16).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In particular, at the beginning of the process, low methane percentages have been registered (15-20%), especially for OPW ensiled for 7 days; subsequently, the percentage increases, reaching values of 60-70% in correspondence of the 20 th day of digestion. During the last days of the experiment, cumulated methane production grows slowly, due probably to the reduction of the available substrate [20][21]. Figure 5 shows the same results of Figure 4, underlining the differences among bottles of different groups, with sometimes pronounced differences even within the same group.…”
Section: Figure 1 Biogas Production During Ensilingsupporting
confidence: 69%
“…The SPME extractions were carried out in three-phase Divinylbenzene/carboxen/polydimethylsiloxane DVB/CAR/PDMS fibre, 50/30 μm (Sigma-Aldrich Australia, catalog number 57347-U), which was designed for analytes with a broad range of polarities (suitable for C2-C20 range) [21] [22] (Sigma-Aldrich Australia, catalog number 57347-U), attached to a manual SPME holder (Supelco Inc.). The fibres were conditioned as recommended by the manufacturer and the supplier specifications before analyses.…”
Section: Apparatus and Equipmentmentioning
confidence: 99%